PENGEMBANGAN E-LKPD INTERAKTIF PADA MATA PELAJARAN MATEMATIKAKELAS VII SMP - Rani Safitri; Fetri Yeni J; Eldarni; Reni Kurnia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The development of this interactive E-LKPD was motivated by students’ low interest in learning mathematics, which is partly caused by the use of monotonous and less engaging printed worksheets. To address this issue, an interactive E-LKPD using Liveworksheets was developed to help teachers create a more engaging and interactive learning atmosphere. This interactive E-LKPD was designed for the Mathematics subject at SMP Negeri 4 Payakumbuh with the aim of fostering enjoyable learning experiences and improving students’ understanding of the material. This study is a Research and Development (R&D) project employing the 4D development model, consisting of the Define, Design, Develop, and Disseminate stages. The product validity was assessed by three validators, including two media experts and one material expert. In addition, a practicality test was conducted on 31 seventh-grade students to determine the practicality level of the developed interactive E-LKPD. The research findings show that the interactive E-LKPD using Liveworksheets obtained a material validation score of 90.6%, indicating a Highly Valid category. Media validation results revealed scores of 97.4% from the first media expert and 96.2% from the second media expert, both categorized as Highly Valid. The practicality test achieved a score of 91.2%, classified as Highly Practical. Therefore, it can be concluded that the developed interactive E-LKPD is valid and practical to be used as a learning medium for seventh-grade Mathematics, particularly on integer and algebra topics.